2020
DOI: 10.1088/1757-899x/821/1/012015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coconut-shell ash as filler and plastic bottle as substitution of porous asphalt mixture

Abstract: Generally, porous asphalt mixtures are having low stability and highly dependent on the quality of asphalt as an aggregate binder, so the innovation of using additive needs to be examined to produce high quality asphalt. In this study, the additive used in asphalt mixtures is plastic bottle waste (Polyethylene Terephthalate/PET) and the use of coconut-shell ash (CS) as filler. This study aims to find out the influence of using PET waste and CS in asphalt porous mixtures which meets its parameter of Cantabro Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Incorporating XPS into porous asphalt mixtures for road construction presents a viable solution that tackles waste IOP Publishing doi:10.1088/1755-1315/1303/1/012037 2 management challenges while promoting sustainable practices [5]. Furthermore, the utilization of ash powder generated from agricultural and industrial activities can serve effectively as filler material in porous asphalt mixtures, thereby mitigating the environmental impact associated with waste generation [3], [6].…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating XPS into porous asphalt mixtures for road construction presents a viable solution that tackles waste IOP Publishing doi:10.1088/1755-1315/1303/1/012037 2 management challenges while promoting sustainable practices [5]. Furthermore, the utilization of ash powder generated from agricultural and industrial activities can serve effectively as filler material in porous asphalt mixtures, thereby mitigating the environmental impact associated with waste generation [3], [6].…”
Section: Introductionmentioning
confidence: 99%
“…Several research studies present some strategies to solve problems with bitumen binder. The use of waste materials like coconut-shell ash, black rice husk ash, and eggshell, which helped researchers to investigate the use of these wastes as a partial replacement for bitumen binder, improves pavement performance and environmental concerns [7,8,9]. Currently, waste material is a big problem in many parts of the world.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that coconut shells and fibers improve stability and rutting resistance. While in another study [ 15 ], coconut shells and plastic bottle waste were analyzed as fillers in PA mixtures. It was suggested that the plastic bottle waste improved the binder drainage and coconut shells, in agreement with the previous study [ 16 ] enhanced the Marshal stability of PA mixtures.…”
Section: Introductionmentioning
confidence: 99%